1857
DOI: 10.1017/s0080456800032269
|View full text |Cite
|
Sign up to set email alerts
|

XXXI.—On New Forms of Marine Diatomaceæ, found in the Firth of Clyde and in Loch Fine

Abstract: In two papers read before this Society, I have very fully described the Diatomaceæ of the Glenshira Sand, which is very remarkable both for the large number of species found in it, which is certainly more than 320, and for the circumstances in which it must have been deposited. There can be no doubt, from the nature of the locality, which I have lately visited, that this bed was formed in the bottom of the Dhu Loch, a shallow fresh-water lake, at that time extending about two miles farther up the valley than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1946
1946
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…However, the sketches in earlier literature did not accurately illustrate the girdle area types for species definition. Examples of this can be seen in the girdle area type pictures of A. granulata (Gregory 1857 , Fig. 96b) and A. proboscidea (Gregory 1857, Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the sketches in earlier literature did not accurately illustrate the girdle area types for species definition. Examples of this can be seen in the girdle area type pictures of A. granulata (Gregory 1857 , Fig. 96b) and A. proboscidea (Gregory 1857, Fig.…”
Section: Discussionmentioning
confidence: 94%
“…To acquire more accurate data on the size of Amphora, natural samples will need to be tested. However, many studies (Gregory 1857, Van Heurck 1896, Péragallo and Péragallo 1908, Cleve-Euler 1953, Levkov 2009) have shown that the same species from different locations can have various sizes. For example, the 70-150 μm cell lengths of A. proteus in England, Belgium, Germany, and Norway (Van Heurck 1896) were much larger than the 15-60 μm cell lengths in the Firth of Clyde and in Loch Fine (Gregory 1857).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apical pore fields at the valve ends correspond to the "unstriated knobs at each end of the valves" of Gregory (1857). The absence of rimoportulae, the valvar striation with virgae, and the chain formation all indicate that the species should form a part of the generic concept of the genus Dimeregramma.…”
Section: Discussionmentioning
confidence: 99%
“…distans' in his ecological studies of Loch Goil. However, N. distans has a symmetrical outline and the raphe is close to the midline of the valve (Gregory, 1857), not eccentric as in the Loch Goil forms. An irregular texturing of the dorsal part of the valve in some of the Goil forms reminded us of H. segmentalis (Brun, 1895), but apart from this no similar diatoms were found illustrated in floras (e.g.…”
Section: Introductionmentioning
confidence: 91%